miR-106a Is Downregulated in Peripheral Blood Mononuclear Cells of Chronic Hepatitis B and Associated with Enhanced Levels of Interleukin-8 - Zhongsi Hong; Haiyu Hong; Jian Liu; Xiaobin Zheng; Mingxing Huang; Chunna Li; Jinyu Xia (Mediators of Inflammation)
Aims. This study aimed to investigate miR-106a expression in peripheral blood mononuclear cells (PBMCs) of chronic hepatitis B (CHB) patients and to analyze the function of miR-106a. Materials and Methods. miR-106a expression levels in PBMCs from 40 healthy controls and 56 CHB patients were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). The luciferase activity assays were used to determine whether miR-106a binds to 3′UTR of IL-8. miR-106a mimics and inhibitors were transfected into healthy PBMCs. IL-8 mRNA and protein levels were detected and determined by qRT-PCR and ELISA, respectively. Results. The qRT-PCR results suggested that the PBMC miR-106a levels were decreased in CHB patients. IL-8 was augmented in CHB patients and was inversely correlated with miR-106a levels. The luciferase activity assays indicated that IL-8 is a target of miR-106a. Exogenous expression of miR-106a could significantly repress IL-8 expression at both mRNA and protein levels in PBMCs, whereas miR-106a inhibitor had the opposite effects. Conclusions. This study suggested that miR-106a is downregulated in PBMCs of CHB patients and that miR-106a may play an important role in CHB by targeting IL-8.